2014
DOI: 10.11646/zootaxa.3814.1.4
|View full text |Cite
|
Sign up to set email alerts
|

A new Amazonian species of Cryptocellus (Arachnida, Ricinulei), with descriptions of its integumental structures and all free-living life stages

Abstract: A new species of Cryptocellus Westwood, 1874 is described, based on males, females and all free-living immature stages. Cryptocellus muiraquitan sp. nov. from Juruti, Pará, Brazil, is a member of the foedus group of species and probably closely related to Cryptocellus icamiabas Tourinho & Azevedo, 2007, C. abaporu Bonaldo & Pinto-da-Rocha, 2003 and C. simonis Hansen & Sørensen, 1904. The new species is illustrated using stereomicroscopy and scanning electron microscopy. The large diversity of integumental stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…They are characterized by having in the anterior region of the prosoma a hinged plate, the cucullus, that acts as a hood covering the mouthparts, by a locking mechanism between the prosoma and the opisthosoma (a trait shared with trigonotarbids, an extinct lineage) that can be uncoupled during mating and egg-laying, and by a modified third leg in males for sperm transfer, among other characters. A total of 76 living Ricinulei species are currently accepted [ 2 , 3 ] in three genera: Ricinoides Ewing, 1929 from tropical West Africa (from The Gambia to Gabon), Cryptocellus Westwood, 1874 from tropical South America and Central America (Guyana to Peru to Honduras), and Pseudocellus Platnick, 1980 from North and Central America (southern USA to Panama) [ 4 ] ( figure 1 ).
Figure 1.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are characterized by having in the anterior region of the prosoma a hinged plate, the cucullus, that acts as a hood covering the mouthparts, by a locking mechanism between the prosoma and the opisthosoma (a trait shared with trigonotarbids, an extinct lineage) that can be uncoupled during mating and egg-laying, and by a modified third leg in males for sperm transfer, among other characters. A total of 76 living Ricinulei species are currently accepted [ 2 , 3 ] in three genera: Ricinoides Ewing, 1929 from tropical West Africa (from The Gambia to Gabon), Cryptocellus Westwood, 1874 from tropical South America and Central America (Guyana to Peru to Honduras), and Pseudocellus Platnick, 1980 from North and Central America (southern USA to Panama) [ 4 ] ( figure 1 ).
Figure 1.
…”
Section: Introductionmentioning
confidence: 99%
“…Despite abundant recent taxonomic work (e.g. [2,3,[5][6][7][8][9][10]), and some phylogenetic and biogeographic studies [11], Ricinulei remains an obscure group, as it was in 1964 when Savory [12] stated that 'the discovery of each new specimen is still something of a zoological triumph'. Seventy-six years ago, Gertsch et al [13] found the first North American Ricinulei and reported that only ca 30 specimens were known for the Americas at the time.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining individuals were found under logs and rocks. We used small sample sizes for the behavioral observations because most ricinuleid species are considered uncommon and only few species have been reported to be locally abundant (e.g., Tourinho et al 2014).…”
Section: Field Capture and Rearingmentioning
confidence: 99%
“…They exhibit unique morphological modifications such as the hood-like cucullus covering the mouthparts dorsally as well as the sexually dimorphic third pair of legs in males which is modified for sperm transfer (e.g., Platnick 2002). Most studies about this group, including the most recent publications, have mainly focused on its taxonomy (e.g., Botero-Trujillo 2014; Valdez-Mondragón and Francke 2011; Tourinho and Saturnino 2010;Tourinho et al 2014), ultrastructure (e.g., Talarico et al 2006Talarico et al , 2008Talarico et al , 2011, biogeography (e.g., Murienne et al 2013) and ecology (e.g., Barreiros et al 2005), while other aspects remain unknown. Indeed, the behavior of ricinuleids relies mostly on occasional observations without detailed analyses of the behavioral patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Ricinulei (hooded tick spiders or tick beetles) have long been one of the least understood arachnid orders, but anatomical studies (Salvatierra & Tourinho, 2016; Salvatierra et al, 2013; Talarico et al, 2005, 2006, 2007, 2009, 2011; Talarico, García Hernández, et al, 2008; Talarico, Palacios‐Vargas, et al, 2008), phylogenetic/biogeographic work (Fernández & Giribet, 2015; Murienne et al, 2013), a plethora of taxonomic descriptions (de Armas, 2017; Botero‐Trujillo, 2014; Botero‐Trujillo et al, 2021; Botero‐Trujillo & Valdez‐Mondragón, 2016; Pinto‐da‐Rocha & Andrade, 2012; Tourinho et al, 2010, 2014; Tourinho & Saturnino, 2010; Valdez‐Mondragón et al, 2018, 2020; Valdez‐Mondragón & Francke, 2011, 2013; Valdez‐Mondragón & Juárez‐Sánchez, 2021), and even behavioral observations (García et al, 2015) have put the group back on the map. For example, when the last catalogue of Ricinulei was published (Harvey, 2003), 55 species had been described, while 81 were reported in the World Ricinulei Catalog (WRC) of 2021 (although the WRC does not include an extra 15 species reported in the most recent taxonomic account of Botero‐Trujillo et al (2021)).…”
Section: Introductionmentioning
confidence: 99%